Antara Rasional dan Emosional: Menguji Peran Flash Sale dan Fear of Missing Out (FOMO) dalam Keputusan Pembelian Skincare Basic Mahasiswa - Mutiara, Prima Dwi; Nasori, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
This study aims to analyze the influence of flash sales and FOMO on the purchasing behavior of basic skincare among university students. Using a quantitative approach with descriptive and correlational methods, data were collected via online questionnaires using a 1-5 Likert scale distributed to 46 students of Universitas Jenderal Soedirman selected through purposive sampling. Data analysis included descriptive statistics, validity and reliability tests, and multiple linear regression. Results indicate that flash sales have a positive and significant effect on purchasing behavior (β = 0.332; p = 0.002), while FOMO does not (β = 0.096; p = 0.299). Simultaneously, both variables significantly influence purchasing behavior (F = 5.697; p = 0.006), yet explain only 17.3% of the variance (Adjusted R² = 0.173). Findings suggest students respond more to price-based promotions than emotional or social pressure, viewing basic skincare as a functional need driven by rational factors like price and suitability.